Economic and circular economy analysis of including potato waste in beef feedlot diets: a Canadian case study - Stephens, Emma C.; Aboagye, Isaac; Mengistu, Genet; McAllister, Tim; Ominski, Kim (Frontiers in Sustainability, 2025)
IntroductionThe present study investigates the combined impact of adding a common agricultural waste by-product alternative feed (cull potatoes) to the diet of feedlot cattle on both economic profitability and greenhouse gas (GHG) emissions.MethodsA standard enterprise budget model for beef feedlots was used to estimate economic impacts of replacing feed grains with cull potatoes in cattle diets in two beef feedlot regions in Canada. We compared economic outcomes with the estimated GHG emissions associated with these production systems, along with the offset potential from diverting cull potatoes from landfill to feed for finishing beef cattle.ResultsInclusion of cull potatoes in beef feedlot diets generated a ‘win-win’ scenario, reducing both the per head feed costs and GHG emissions associated with finishing beef cattle. Diversion of cull potatoes from landfill to feed further offset beef finishing GHG emissions by more than 65% and up to 89% for scenarios with higher inclusion rates of cull potatoes.DiscussionIncreasing the use of palatable waste by-products like cull potatoes in feedlot diets can potentially reduce both the cost of production and GHG emissions, thereby improving both environmental sustainability and profitability. Facilitating greater diversion of agricultural by-products to livestock can enable the ruminant sector to realize its full potential to upcycle waste by-products in a circular bioeconomy.